Comparison of effects of SGLT-2 inhibitors and GLP-1 receptor agonists on cardiovascular and renal outcomes in type 2 diabetes mellitus patients with/without albuminuria: A systematic review and network meta-analysis. (January 2022) - Kawai, Yuki; Uneda, Kazushi; Yamada, Takayuki; Kinguchi, Sho; Kobayashi, Kazuo; Azushima, Kengo; Kanaoka, Tomohiko; Toya, Yoshiyuki; Wakui, Hiromichi; Tamura, Kouichi
Abstract: Aims: It remains unclear which sodium-glucose cotransporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are most effective for preventing cardiovascular and renal events in type 2 diabetes mellitus (T2DM) patients, depending on the presence of albuminuria. We conducted a network meta-analysis to compare the efficacy of these two drug classes in T2DM patients with/without albuminuria. Methods: We searched the Medline, EMBASE, Cochrane Library databases, and gray literature up to April 20, 2021. We included randomized controlled trials that reported the risk of major adverse cardiovascular events (MACE) and composite of renal outcomes in T2DM. Results: A total of nine studies (81, 206 patients) were included. In patients with/without albuminuria, SGLT-2 inhibitors did not significantly reduce the risk of MACE compared with GLP-1 RAs (risk ratio [RR] [95% confidence interval]; 0.96 [0.82–1.12] and 0.94 [0.81–1.10], respectively). In contrast, compared with GLP-1 RAs, SGLT-2 inhibitors were associated with significantly lower renal risk in both patients with/without albuminuria (RR [95% CI]; 0.75 [0.63–0.89] and 0.59 [0.44–0.79], respectively). Conclusions: SGLT-2 inhibitors may be superior to GLP-1 RAs for renal outcomes in T2DM patients with/without albuminuria, although there was no difference in the risk of MACE.